Preparation and characterization of a quaternary ammonium derivative of konjac glucomannan - Yu, Huiqun; Huang, Yihong; Ying, Hou; Xiao, Chaobo (Carbohydrate polymers, 2007)
Cationic derivatives of konjac glucomannan (KGM) were prepared by reacting KGM with 3-chloro-2-hydroxypropyltrimethylammonium chloride (CHPTAC) in presence of sodium hydroxide. The chemical structures of derivative were characterized by use of elemental analysis, FTIR and 13C NMR spectroscopy and static light scattering technique. The results revealed that the degree of substitution (DS) of quaternized konjac glucomannan (QKGM) could be controlled by adjusting the weight ratio of CHPTAC to KGM and the degradation of KGM molecules occurred during quaternization. Thermogravimetric analysis showed that the thermal stability of QKGM was lower than that of KGM. Rheological properties of KGM and QKGM were evaluated in steady and dynamic shear. The flow data were fitted fairly well by the Cross equations and various parameters were calculated. Dynamic shear tests demonstrate that highly modified KGM behaved like dilute solution, while unmodified KGM displayed entanglement network behavior. Significant shear-thinning effects and deviations from the Cox–Merz rule are observed in present study. In vitro antimicrobial activity assessment exhibited QKGM showed pronounced inhibitory effect against the three bacteria and four fungi investigated, but no Pseudomonas aeruginosa and Aspergillus niger inhibition. The improved functionalities of the derivative might be explained by its polycationic characteristics.